Botany for dummies ebook - Fester Kratz, Rene (Dummies., 2011)
The easy way to score your highest in botany Employment of biological scientists is projected to grow 21% over the next decade, much faster than the average for all occupations, as biotechnological research and development continues to drive job growth. Botany For Dummies gives you a thorough, easy-to-follow overview of the fundamentals of botany, helping you to improve your grades, supplement your learning, or review before a test. Covers evolution by natural selection Offers plain-English explanations of the structure and function of plants Includes plant identification and botanical phenomenon Tracking a typical course in botany, this hands-on, friendly guide is your ticket to acing this required course for your major in biology, microbiology, zoology, or elementary education.